Hubungan Hukum Peradilan Agama dan Kantor Urusan Agama, Studi Kasus KUA Kotagede - Sutantriyati, Ari; Hasanudin, Alhumairah Hayati; Ramadhan, Dino Wahyu; Firmansyah, Ahmad Fatur; Aman, Herismon US; Zaeni, Annas Tatia Nurul; Kiflan, Kiflan; Rahman, Ahmad Syafii (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
The research results in the Field Work Practice of students of the Family Law Study Program of the Faculty of Islamic Studies of UCY in the Kotagede Ministry seek to explore the binding legal relationship between the Religious Court and KUA based on the implementation of KUA services to the community. This research uses the Participatory Action Research method where students are actively involved during the research with a case study approach. KUA is the unit in the Ministry of Religious Affairs and has a legal relationship as the administrative implementer of decisions and provisions of religious courts in the fields of marriage, divorce, reconciliation, and waqf. Other Sharia services from KUA include product halal certification, mosque management, and anti-corruption counseling in the family, all of which are in accordance with Islamic law regulations in force in Indonesia.